Development of a Model for Preparing an Exercise Program to Improve the Physical Condition of Table Tennis Club Athletes in the City of Lubuklinggau Through the Application - Dinda Dwi Cahyuni; Iyakrus Iyakrus; Wahyu Indra Bayu (UNIB Press, 2022)
This study aims to determine whether the development of an exercise program formulation model can improve the physical fitness of table tennis athletes through valid and practical applications. This research method uses the Borg & Gall model, and data collection uses observation, tests, and questionnaires. The data analysis in this study consisted of an analysis of the validity, practicality, and effectiveness. The findings of this study are the product resulting from the development of an exercise program suitable for mass use. This is reinforced by the results of expert evaluations of table tennis practitioners, the responses of coaches and athletes, as well as physical fitness tests for athletes. The results of the validity state that the product is categorized as very good, with a very high level of practicality for the response of coaches and athletes, and the preparation of an effective training program to improve the physical fitness of athletes.